Management of Anticoagulant Treatment and Anticoagulation-Related Complications in Nonagenarians - Giustozzi, Michela; Castellucci, Lana A.; Barnes, Geoffrey D. (Hämostaseologie, 2020)
Given the aging population, the burden of age-dependent diseases is growing. Despite this, elderly patients are often underrepresented in clinical trials and little data are available on current anticoagulant management and outcomes in this unique population, especially those aged 90 years or older. There is uncertainty, and a fear of “doing harm,” that often leads to de-prescription of antithrombotic agents in nonagenarian patients. Decision-making concerning the use of anticoagulant treatment needs to balance the risk of thrombotic events against the risk of major bleeding, especially intracranial hemorrhage. In this perspective, the development of direct oral anticoagulants (DOACs), acting as direct and selective inhibitors of a specific step or enzyme of the coagulation cascade, has dramatically changed oral anticoagulant treatment. In fact, given the lower incidence of intracranial hemorrhage, the favorable overall efficacy and safety, and the lack of routine monitoring, DOACs are the currently recommended anticoagulant agents for the treatment of both atrial fibrillation and venous thromboembolism even in very elderly patients. However, given the limited data available on the management of anticoagulation in nonagenarians, a few unanswered questions remain. In this review, we focused on recent evidence for anticoagulant treatment in atrial fibrillation and venous thromboembolism along with management of anticoagulation-related bleeding in nonagenarians.
Keywords: anticoagulants; atrial fibrillation; nonagenarians; oldest age; venous thromboembolism